1994
DOI: 10.1111/j.1432-1033.1994.tb20088.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen‐Defence Gene prp1–1 from Potato Encodes an Auxin‐Responsive Glutathione S‐Transferase

Abstract: Genetic studies have previously implicated the prp1 gene family in the defence of potato against infection with the late blight fungus Phytophthora infestans. Here, we show that the concentrations of PRP1 mRNA as well as protein rapidly increase in potato leaves after fungal infection and stay at high levels during an extended period of the infection cycle. After separation of subcellular components by differential centrifugation, PRP1 protein was identified in the cytosolic fraction. Expression studies with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 45 publications
1
61
0
Order By: Relevance
“…Furthermore, increased transcription of specific SOD and catalase genes may occur to ensure that maximal enzymatic activity is maintained within the appropriate cellular compartments (Bowler et al, 1994). For example, the expression of glutathione peroxidase, glutathione S-transferase, and polyubiquitin genes has been detected in incompatible interactions (Mauch and Dudler, 1993;Hahn and Strittmatter, 1994;Levine et al, 1994). Glutathione peroxidase activity can block cell death in mammalian systems (Hockenbery et al, 1993), whereas glutathione S-transferase detoxifies the products of lipid membrane peroxidation and other products of cellular oxidative stress (Berhane et al, 1994).…”
Section: Slgnallng Mechanismsmentioning
confidence: 99%
“…Furthermore, increased transcription of specific SOD and catalase genes may occur to ensure that maximal enzymatic activity is maintained within the appropriate cellular compartments (Bowler et al, 1994). For example, the expression of glutathione peroxidase, glutathione S-transferase, and polyubiquitin genes has been detected in incompatible interactions (Mauch and Dudler, 1993;Hahn and Strittmatter, 1994;Levine et al, 1994). Glutathione peroxidase activity can block cell death in mammalian systems (Hockenbery et al, 1993), whereas glutathione S-transferase detoxifies the products of lipid membrane peroxidation and other products of cellular oxidative stress (Berhane et al, 1994).…”
Section: Slgnallng Mechanismsmentioning
confidence: 99%
“…These include the parsley Pr-1 genes (Rushton et al, 1996), the potato Gst1 (a glutathione Stransferase; Hahn and Strittmatter, 1994) and Sth-2 genes (Pr-10-like; Matton et al, 1993), the grapevine Vst1 gene involved in phytoalexin biosynthesis (Schubert et al, 1997), the asparagus . In the Arabidopsis Pr-1 promoter a W-box like sequence was identified that seemed to be involved in negative regulation of inducible expression .…”
Section: Regulatory Elements Of Pathogen Responsive Genes and Transcrmentioning
confidence: 99%
“…The ORFs were constructed into the vector pQE60 (Qiagen, Hilden) for expression in E. coil, and into pBSexp (da Costa e Silva et aL, 1993) for expression by coupled in vitro transcription/ translation. The constructs expressing GST and rMYB305 were kindly provided by G. Strittmatter and C. Martin, respectively (Hahn and Strittmatter, 1994;Jackson et aL, 1991). All plasmid constructions were verified by sequencing.…”
Section: Plasmids and Cloning Proceduresmentioning
confidence: 99%